ANALISIS RASIO PROFITABILITAS GROSS PROFIT MARGIN DAN RETURN ON ASSET SEBAGAI ALAT UKUR UNTUK MENILAI KEEFEKTIFAN KINERJA KEUANGAN PADA PT. KIMIA FARMA (PERSERO), TBK TAHUN 2013-2017 - Putri Sarirati; Devi Choirinnisa (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
Based on the calculation of Gross Profit Margin tends to show an increase every year, namely from 2013 to 2017, overall an average increase of 1.55%, with an R Square level of 0.85 or 85%. Return on Assets experienced instability in the period 2013 - 2017 due to the increase in cost of goods sold. The overall decrease is an average of 0.81% with the level of R Square 0.94 or 94%. A decrease of 0.51% occurred in 2013 of 8.58% until 2014 it became 8.07%. In 2015 it decreased by 0.46% to 7.61%. And again, decreased in 2016 by 1.81% to 5.80%. Kimia Farma declined again in 2017 by 0.44% to 5.36%. Based on the results of the Regression Test for Gross Profit Margin and Return on Assets variables meet the Normality Test, in terms of Autocorrelation Test R Square level of 0.960 or 96% effect as a measurement tool to assess the effectiveness of financial performance, in terms of Homoscedasticity Test Homoscedasticity did not occur and in terms of Multicollinearity, Test Multicollinearity disorder does not occur or in other words the Regression model is free from the symptoms of Multicollinearity. The final result of this study is the profitability of PT. Kimia Farma (Perseo) Tbk, during the last five years experienced a fluctuation or recollection and decline. The level of profitability or the company's ability to make a profit has decreased in the past year. The best level of profitability in years 2013. However, PT. Kimia Farma (Persero) Tbk has been able to pass 2017 which is full of challenges, with a record that the company's operational performance is very satisfying even though in terms of financial performance has decreased compared to the realization of performance in 2013.